Hydration of human and bovine serum albumin complexes with chlorophyllin investigated by differential ehf dielectrometry - Pesina, D. A.; Kashpur, V. A.; Khorunzhaya, O. V.; Shestopalova, A. V. (Biophysical Bulletin, 1970)
This study is designed to examine the hydration effects accompanying the interaction betweenchlorophyllin (CHLN), a potent inhibitor of experimental carcinogenesis, and human and bovine serumalbumins (HSA and BSA) in aqueous solutions using differential dielectric method. This method allowsstudying both dielectric characteristics and hydration of the compounds under investigation. We showthat for both complexes the process of complex formation is accompanied by changes of dielectricparameters. We also present calculations of the hydration of proteins and their complexes with ligand,which were carried out basing on the model concepts. We found that formation of CHLN complex withfatty acids free BSA is accompanied by a significant decrease of hydration while no notable hydrationchanges takes place upon formation of CHLN complex with HSA containing fatty acids. The formereffect indicates that redistribution of free and bound water molecules takes place during the formation ofthe complex. The possible causes of effects observed are discussed.